Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

From solvent-tailored carbon dots to a practical sensor array: fingerprint discrimination and quantification of azo dyes in beverages - Zhi-Min Zhi; Zong-Mei Huang; Cong-Ting Wu; Jing Li; Yanting Song; Lu-Shuang Li (Food Chemistry, 2026)

Effects of the Biosurfactant Rhamnolipid on the hygroscopicity and cloud condensation nuclei activity (CCN) of ammonium sulfate aerosols - Wenxu Fang; Zhijun Wu; Taomou Zong; Yanting Qiu; Xiangxinyue Meng; Jingchuan Chen; Zeyu Feng; Junrui Wang; Linghan Zeng; Zheng Chen; Zirui Zhang; Yu Xie; et al. (Atmospheric Research, 2026)

A multimodal vector sensor enabled by 3D-printed coplanar interdigital electrodes for dynamic and static bending detection - Shihao Song; Hao Yin; Chenhui Jiang; Yanting Li; Yiping Guo (Chemical Engineering Journal, 2026)

Magnetic resonance imaging for rapid, noninvasive and accurate assessment of ovarian maturation in live Channa argus (Cantor, 1842) - Wenqian Sun; Weiyin Vivian Liu; Xingyu Chen; Guangcan Lin; Hao Li; Yanting Song; Chengdong Peng; Wen Xiong; Yu Peng; Shangong Wu; Shouqi Xie; Sovan Lek; et al. (Aquaculture, 2026)

Diesel exhaust induces hepatic steatosis by activating the aryl hydrocarbon receptor/CD36 pathway - Qian Song; Xueying Zhang; Yanting Li; Zixuan Liang; Ao Han; Xiaoran Wei; Xiaowen Tang; Juntong Wei; Wei Han; Shanfa Yu; Hongna Zhang; Yuxin Zheng (Journal of Hazardous Materials, 2026)

Combustion and explosion reaction kinetics of thermal runaway gases from three lithium-ion batteries with different metal-oxide cathodes - Song Lin; Yanting Cao; Yunhao Li; Kai Zheng; Yan Tang; Juncheng Jiang (Fuel, 2026)

Silencing of the Superaquaporin LvAQP11 Disrupts Salinity Tolerance, Molting Cycle, and Myofibril Organization in Litopenaeus vannamei - Zhongkai Wang; Guanghao Song; Shikui Zhang; Long Zhang; Beibei Wang; Kunpeng Zhao; Yanting Cui; Fei Liu; Renjie Wang; Yuquan Li (Fishes, 2025)
The Pacific white shrimp (Litopenaeus vannamei), a euryhaline crustacean of significant economic importance, is widely cultivated for its adaptability to diverse salinity levels. Aquaporins (AQPs) are membrane channel proteins that mediate the transport of water and small solutes across biological membranes. Among them, aquaporin 11 (AQP11) is classified as a superaquaporin, and its physiological roles remain unclear. In this study, RNA interference (RNAi) was employed to silence AQP11 expression in L. vannamei, followed by RNA-seq analysis to investigate transcriptomic responses. Differentially expressed genes (DEGs) were identified by comparing dsAQP11 and control groups. The LvAQP11 knockdown significantly increased mortality to 76.7% under acute high-salinity stress (50‰) but not under low-salinity conditions (10‰). Transcriptomic analysis revealed that LvAQP11 deficiency disrupted amino acid metabolism pathways and triggered endoplasmic reticulum stress, as evidenced by the upregulation of proteasome subunits and unfolded protein response genes. Furthermore, silencing LvAQP11 delayed molting progression in the premolt stages, accompanied by the significant upregulation of molt-inhibiting hormone (LvMIH1/5) and downregulation of retinoic acid X receptor (LvRXR). The long-term silencing of LvAQP11 did not affect the weight gain rate (WGR) or the specific growth rate (SGR) but induced muscle fiber disorganization and significantly increased muscle water content. RNA sequencing identified enriched carbohydrate and chitin metabolism pathways, indicating disrupted cytoskeletal dynamics and extracellular matrix integrity. Through this study, we elucidate the crucial roles of LvAQP11 in osmoregulation, molting, and muscle integrity in L. vannamei, providing novel insights into the multifunctional nature of superaquaporins beyond water transport.

Exploring the mechanisms of torularhodin in alleviating diabetic kidney disease: a microbiome and metabolomics approach through the gut-kidney axis - Wenlong Deng; Yi Guo; Qigui Mo; Jiaqi Liu; Yanting Su; Zhihao Wei; Runtao Ma; Jiaqi Chen; Yue Song; Tianqi Chen; Peng Wang; Wei Yu; et al. (Food Research International, 2025)

Targeting FOXK2 in triple-negative breast cancer: Role of the P53/MCAS1/miR-211–5p regulatory axis - Zankai Wu; Yanting Zhang; Dandan Xiang; Tian Li; Yiping Gong; Qibin Song; Jin Hu (Functional & Integrative Genomics, 2025)

Caulerpa lentillifera extract alleviates the chronic diquat-induced liver oxidative damage in zebrafish (Danio rerio) in association with Nrf2 and AMPK/mTOR signaling pathway - Xiang Lin; Xiaocen Xie; Qijun Fu; Zhongqun Liu; Ye Xiao; Yongqiang Wang; Haiping Li; Xi Xie; Rong Wang; Yingxia Zhang; Yanting Song; Wenting Hu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Impacts of aerosol acidity and liquid water content on secondary inorganic aerosol pollution in East Asian megacities: Beijing and Seoul - Junrui Wang; Zhijun Wu; Tao Qiu; Ruiqi Man; Taomou Zong; Yanting Qiu; Wenxu Fang; Shiyi Chen; Dapeng Liang; Mijung Song; Junyoung Ahn; Jiyi Lee; et al. (Atmospheric Environment, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Polyethylene glycolated chitosan nanocarriers: integrated extraction, stabilization and colonic targeted delivery of tea polyphenols for anti-inflammatory and prebiotic effects - Wenzhi Lei; Jiangling Song; Yanting Chen; Xingnan Wang; Hongcai Li; Zhenpeng Gao (Food Bioscience, 2025)

Insight into C6F12O fire suppression mechanism on coaxial n-heptane flame: Combined experimental and ReaxFF molecular dynamics simulation - Haoran Xing; Song Lu; Jiulong Tao; Yanting Zhou; Junchao Zhao; Heping Zhang (Process Safety and Environmental Protection, 2025)

Advancing the Understanding of Infilled Joint Shear Behavior: A Review of Modeling, Measurement, and Influential Factors - Leibo Song; Zhiyong Bai; Quan Jiang; Binghe Zhu; Gang Wang; Yanting Gu (Rock Mechanics and Rock Engineering, 2025)

Efficient enrichment and distinguishable analysis of microcystin congeners by combining oriented imprinting with array sense strategy - Yanqiao Zhu; Yuanxia Xu; Jinyu Cao; Yanting Wang; Xueping Hu; Xingliang Song (Journal of Hazardous Materials, 2025)

Impact of adding sorghum tannin on volatile compounds and fermentation products of whisky - Wanlong Lu; Tingnan Song; Wenping Lei; Yanting Li; Jingming Li; Jinkun Du (Food Bioscience, 2025)

Exploring the Correlation Between Varied Serum Iodine Nutritional Levels and Anti-Thyroglobulin Antibodies - Qiuyi Song; Tingting Xu; Yu Wang; Hongyan Wei; Feng Tan; Yanting Chen; Fang Fang; Tingkai Cui; Ziyun Pan; Xiaohui Guo; Wen Chen; Jun Shen; et al. (Biological Trace Element Research, 2025)

Enantioselective toxicity effect and mechanisms of bifenthrin enantiomers on normal human hepatocytes - Yiyi Liao; Yuhang Gao; Qigeng Chen; Mingyu Pan; Makoto Tsunoda; Fuping Liu; Yingxia Zhang; Wenting Hu; Lu-shuang Li; Haimei Yang; Yanting Song (Food and Chemical Toxicology, 2024)

Impact of biomass burning on PM2.5 and organic aerosol: Quantitative estimates and spatial distributions in four Northeast Asian sites - Jayant Nirmalkar; Ji Yi Lee; Kwangyul Lee; Junyoung Ahn; Yanting Qiu; Zhijun Wu; Amgalan Natsagdorj; Kyoung-Soon Jang; Changhyuk Kim; Mijung Song (Atmospheric Environment, 2024)

Metabolomics provides insights into the alleviating effect of dietary Caulerpa lentillifera on diquat-induced oxidative damage in zebrafish (Danio rerio) liver - Xiang Lin; Zhongqun Liu; Ye Xiao; Xiaocen Xie; Yongqiang Wang; Haiping Li; Rong Wang; Xi Xie; Yingxia Zhang; Yanting Song; Wenting Hu (Aquaculture, 2024)

SoyOmics: A deeply integrated database on soybean multi-omics - Yucheng Liu; Yang Zhang; Xiaonan Liu; Yanting Shen; Dongmei Tian; Xiaoyue Yang; Shulin Liu; Lingbin Ni; Zhang Zhang; Shuhui Song; Zhixi Tian (Molecular Plant, 2023)

Secondary aerosol formation drives atmospheric particulate matter pollution over megacities (Beijing and Seoul) in East Asia - Yanting Qiu; Zhijun Wu; Ruiqi Man; Taomou Zong; Yuechen Liu; Xiangxinyue Meng; Jingchuan Chen; Shiyi Chen; Suxia Yang; Bin Yuan; Mijung Song; Changhyuk Kim; et al. (Atmospheric Environment, 2023)

Anion-exchange assisted sequential deposition for stable and efficient FAPbI3-based perovskite solar cells - Xinning Jiao; Wei-Min Gu; Yanting Xu; Ke-Jian Jiang; Guanghui Yu; Qing-Wu Zhang; Cai-Yan Gao; Cai-Ming Liu; Xin-Heng Fan; Lian-Ming Yang; Yanlin Song (Chemical Engineering Journal, 2023)

Does the promotion pressure on local officials matter for regional carbon emissions? Evidence based on provincial-level leaders in China - Xiude Chen; Yanting Ke; Huiyang Li; Yazhi Song; Yulian Peng (Environmental Geochemistry and Health, 2022)

Metabolomics analysis of the potential toxicological mechanisms of diquat dibromide herbicide in adult zebrafish (Danio rerio) liver - Ye Xiao; Xiang Lin; Meilan Zhou; Tianyu Ren; Ruili Gao; Zhongqun Liu; Wenjing Shen; Rong Wang; Xi Xie; Yanting Song; Wenting Hu (Fish Physiology and Biochemistry, 2022)

Flavonoids improve drought tolerance of maize seedlings by regulating the homeostasis of reactive oxygen species - Baozhu Li; Ruonan Fan; Guiling Sun; Ting Sun; Yanting Fan; Shenglong Bai; Siyi Guo; Shiquan Huang; Jiong Liu; Hui Zhang; Pengtao Wang; Xiaohong Zhu; et al. (Plant and Soil, 2021)
Background and aims As drought threatens the yield and quality of maize ( Zea mays L.), it is important to dissect the molecular basis of maize drought tolerance. Flavonoids, participate in the scavenging of oxygen free radicals and alleviate stress-induced oxidative damages. This study aims to dissect the function of flavonoids in the improvement of maize drought tolerance. Methods Using far-infrared imaging screening, we previously isolated a drought overly insensitivity ( doi ) mutant from an ethyl methanesulfonate (EMS)-mutagenized maize library and designated it as doi57 . In this study, we performed a physiological characterization and transcriptome profiling of doi57 in comparison to corresponding wild-type B73 under drought stress. Results Under drought stress, doi57 seedlings displayed lower leaf-surface temperature (LST), faster water loss, and better performance in growth than B73. Transcriptome analysis reveals that key genes involved in flavonoid biosynthesis are enriched among differentially expressed genes in doi57 . In line with these results, more flavonols and less hydrogen peroxide (H 2 O 2 ) were accumulated in guard cells of doi57 than in those of B73 with the decrease of soil water content (SWC). Moreover, the capacity determined from doi57 seedling extracts to scavenge oxygen free radicals was more effective than that of B73 under the drought treatment. Additionally, doi57 seedlings had higher photosynthetic rates, stomatal conductance, transpiration rates, and water use efficiency than B73 exposed to drought stress, resulting in high biomass and greater root/shoot ratios in doi57 mutant plants. Conclusion Flavonoids may facilitate maize seedling drought tolerance by lowering drought-induced oxidative damage as well regulating stomatal movement.

Identification and association of novel lncRNA pouMU1 gene mutations with chicken performance traits - Tuanhui Ren; Yanting Zhou; Yu Zhou; Weihua Tian; Zhenzhen Gu; Song Zhao; Yadi Chen; Ruili Han; Xiaojun Liu; Xiangtao Kang; Zhuanjian Li (Journal of Genetics, 2017)

MicroRNA-27a/b mediates endothelin-1-induced PPARγ reduction and proliferation of pulmonary artery smooth muscle cells - Xinming Xie; Shaojun Li; Yanting Zhu; Lu Liu; Yilin Pan; Jian Wang; Wenhua Shi; Yang Song; Lan Yang; Li Gao; Weijin Zang; Manxiang Li (Cell and Tissue Research, 2017)